Psychological and neurological benefits of high-quality nursing for postoperative hypertensive intracranial hemorrhage patients - Feng, Lili; Zhu, Lanli; Wang, Bing (Frontiers in Neurology, 2025)
ObjectivesHigh-quality nursing, defined as evidence-based, patient-centered care that integrates standardized physical care with individualized psychological support, epitomizes superior nursing service delivery. The present study aimed to investigate the effects of High-quality nursing intervention on neurological function, psychological state, and quality of life in postoperative patients with hypertensive intracranial hemorrhage (ICH).MethodsThis study enrolled patients who had undergone surgery for ICH between August 2019 and January 2025. Patients were randomly assigned into two cohorts: an intervention group and a control group. The control group received standard conventional nursing care, while the intervention group underwent high-quality nursing interventions. Comparative analyses were conducted between the two groups regarding various parameters, including neurological function, assessed via the National Institutes of Health Stroke Scale (NIHSS) and the Barthel Index scores; psychological well-being, measured through the Self-Rating Anxiety Scale (SAS) and the Self-Rating Depression Scale (SDS) scores; and quality of life, evaluated using the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36). Additionally, patient satisfaction and the incidence of complications were monitored and compared before and after the intervention.ResultsThe results indicated that the observation group exhibited superior outcomes compared to the control group following the intervention, as evidenced by reduced NIHSS scores and elevated BI scores. Post-intervention, both groups experienced a decline in the scores for the SAS and the SDS, with a notably greater reduction observed in the observation group (both p < 0.05). Furthermore, after the intervention, improvements were noted in all dimensions of the SF-36 for both groups, yet the observation group demonstrated a more pronounced enhancement (p < 0.05). Additionally, the observation group reported a lower incidence of complications and higher levels of nursing satisfaction.ConclusionHigh-quality nursing for patients recovering from hypertensive ICH post-surgery has been shown to have an indirect influence on neurological recovery by alleviating adverse psychological conditions and elevating overall quality of life. This approach is associated with a minimal rate of complications and a high level of nursing satisfaction.